2019
DOI: 10.1108/ijoem-01-2018-0034
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the size of the black economy: new evidence from India

Abstract: Purpose The issue of black economy has long been debated in India and it has been one of the key targets of policy action from last four decades. The debate is further fueled by demonetization of higher currency notes in the country. In this context, the purpose of this paper is to estimate the size of black economy in India for the period 1970–2017. Design/methodology/approach A currency demand approach is adopted for this purpose. The test of structure break indicates for a break in the system; therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…Such influence is bigger in developing countries than transaction economies. Sharma (2019) revealed that several economic changes including taxation, legislation and industrial licensing have sharply reduced the size of shadow economy to below 15% of official GDP in the Indian economy in the last two decades. Pathak et al (2016) found that informal institutions are negatively related to the overall economic involvements in emerging economies.…”
Section: Introductionmentioning
confidence: 99%
“…Such influence is bigger in developing countries than transaction economies. Sharma (2019) revealed that several economic changes including taxation, legislation and industrial licensing have sharply reduced the size of shadow economy to below 15% of official GDP in the Indian economy in the last two decades. Pathak et al (2016) found that informal institutions are negatively related to the overall economic involvements in emerging economies.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of dealing with electronic money needs to be dealt timely, with the help of strong technological infrastructure (de Almeida et al , 2018). The size of black economy was estimated and analyzed to evaluate the decision of demonetization (Sharma, 2019).…”
Section: Content Analysismentioning
confidence: 99%
“…Jendela pasca-peristiwa mempersepsikan CAR negatif pada pemilu pertama dan kedua, dan CAR positif pada dua pemilu terakhir, dan ditemukan bahwa perubahan pemenang pemilu tidak menyebabkan perbedaan besar pada CAR, serta tidak ditemukan hasil yang signifikan ketika mengendalikan inflasi dan suku bunga (Saad & Bouraoui, 2019). Sharma (2019) menunjukkan bahwa ekonomi India memiliki ekonomi hitam yang cukup besar, dimana pada awal 1970-an ketika tarif pajak di India secara signifikan lebih tinggi, perkiraan ekonomi hitam berada di atas 30 persen dari produk domestik bruto (PDB), dan berbagai reformasi ekonomi termasuk perpajakan, regulasi dan perizinan industri telah secara drastis mengurangi ukuran hingga di bawah 15 persen dari PDB resmi dalam dua dekade terakhir.…”
Section: Tinjauan Literaturunclassified